Disentangling the nuances of diversity ideologies - Russell Pascual, Nicole; Kirby, Teri A.; Begeny, Christopher T. (Frontiers in Psychology, 2024)
Objectives: Minoritised racial groups typically report greater psychological engagement and safety in contexts that endorse multiculturalism rather than colourblindness. However, organisational statements often contain multiple (sub)components of these ideologies. This research broadens our understanding of diversity ideologies in the real-world by: (1) mapping out the content of real-world organisational diversity ideologies (2) identifying how different components tend to cluster in real-world statements and (3) presenting these statements to minoritised group members (Study 2) to test how these individual components and clusters are perceived (e.g., company interest, value fit).Methods: 100 US university statements and 248 Fortune 500 company statements were content coded, and 237 racially minoritised participants (Mage = 28.1; 51.5% female; 48.5% male) rated their psychological perceptions of the Fortune 500 statements.Results: While universities most commonly frame diversity ideologies in terms of value-inequality, companies focus more on value-in-individual differences. Diversity rationales also differ between organisations, with universities focusing on the moral and business cases almost equally, but companies focusing on the business case substantially more. Results also offered preliminary evidence that minoritised racial group members reported a greater sense of their values fitting those of the organisation when considering organisations that valued individual and group differences.Conclusions: These are some of the first studies to provide a nuanced examination of the components and clusters of diversity ideologies that real-world organisations are using, ultimately with implications for how we move forward in studying diversity ideologies (to better reflect reality) and redesigning them to encourage more diverse and inclusive organisations.